Exploring the pregnant women's perspective of late booking of antenatal care services at Mbekweni Health Centre in Eastern Cape, South Africa - Ramprakash Kaswa; George F.D. Rupesinghe; Benjamin Longo-Mbenza (AOSIS, 2018)
Background: Antenatal care (ANC) services are the gateway for integrated management of several conditions that adversely affect the mother and foetus. More stillbirths than neonatal deaths in South Africa are a reflection of poor quality ANC services.   Aim: The primary aim of this study was to explore the reasons for late booking, and also to determine pregnant women's knowledge, perceptions and attitude towards antenatal care services they receive in Mthatha area in Eastern Cape, South Africa.   Setting: This was a qualitative study, conducted at Mbekweni Health Centre in the King Sabata Dalindyebo (KSD) subdistrict municipality of the Eastern Cape Province.   Methods: This qualitative study consisted of selected pregnant women who presented after 19 weeks of gestation at Mbekweni Health Centre. Data were collected through two different methods, namely, semi-structured interviews and focus group discussions were used until saturation of the themes were reached. The interviews were transcribed verbatim and thematic analyses were undertaken.   Results: Twenty women participated in the study. They were diverse in terms of age 18-41 years, gravidity 1-6 and time of ANC booking 20-28 weeks. The interviews identified a variety of personal, service and organisational reasons for late ANC booking. The themes identified for late ANC bookings were: health care system related issues, socio-economic factors, women's perceptions and knowledge, and failure of family planning services.   Conclusions: Women's beliefs, knowledge and perceptions regarding antenatal services outweigh the perceived benefit of early ANC visit. The majority of women had lack of knowledge of contraception, early signs of pregnancy, purpose, timing and benefits of ANC visit.